UMNO dan PAS dalam Persaingan Politik Sekuler-Islam di Malaysia - Andri, Adetia (Warisan: Journal of History and Cultural Heritage, 2022)
This article aims to look at the political competition between the United Malay National Organization (UMNO) and the Se-Malaysia Islamic Party (PAS) in political dynamics in Malaysia. These two parties are the two largest parties in Malaysia which both consider themselves to represent the voices of the Malay-Islamic community. In writing, this article uses historical research methods in four steps: heuristics, criticism, verification, and historiography, using a political approach. This approach is used to view a historical event from a political point of view. While in terms of data collection techniques, this article uses library research to collect sources related to the topics discussed. The results of the study show that, since their inception, UMNO and PAS have experienced differences in their political goals. UMNO prioritizes the Malay side of its political strategy, while PAS makes Islam its main strategy. These two parties are trying to win most ethnic Malay votes as the largest ethnic group in Malaysia. Mutual claims and criticisms continue to be carried out by the two parties. Another result is that competition between UMNO and PAS has implications for political stability in Malaysia. The arrest of political opponents between the two parties is unavoidable, resulting in the erosion of the Malay majority vote in the Malaysian general election.